2022
DOI: 10.1128/spectrum.00320-22
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Diverse Acetyltransferase-Type Toxin-Antitoxin Loci in Klebsiella pneumoniae

Abstract: Elucidating the roles of multifaceted GNAT-RHH TA loci is essential for understanding how these TAs interact among themselves. Recently, the reaction mechanisms and structures of several GNAT-RHH pairs have been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…A total of 364, 100, and 2,050 plasmids were classified as ARG-carrying, virulent, and other plasmids, respectively. Of the 2,514 plasmids, 3,164 putative type II TA loci have been predicted [ 34 ]. Kruskal–Wallis one-way ANOVA showed that, overall, virulence plasmids had significantly ( P < 0.001) more TA loci than ARG-carrying and other plasmids ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 364, 100, and 2,050 plasmids were classified as ARG-carrying, virulent, and other plasmids, respectively. Of the 2,514 plasmids, 3,164 putative type II TA loci have been predicted [ 34 ]. Kruskal–Wallis one-way ANOVA showed that, overall, virulence plasmids had significantly ( P < 0.001) more TA loci than ARG-carrying and other plasmids ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among 3,164 putative type II TA loci predicted in the plasmids, 6% ( n = 176) were RES-Xre, which ranked it as the fifth most common type II TA family in the K. pneumoniae’s plasmids[ 34 ]. The predominant sequence types (STs) of K. pneumoniae carrying the virulence plasmids were ST11 ( n = 32) and ST23 ( n = 20) (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, in some isolates of E. coli , plasmid-encoded AtaT toxin of the ataRT toxin-antitoxin cassette was inhibited by chromosomal AtaR antitoxin [ 80 ]. Moreover, Gog and co-workers observed cross-interactions between the KacA3 antidote located on a plasmid and chromosomal KacT2 toxin in Klebsiella pneumoniae [ 121 ]. Weak interactions were also identified between the Kid toxin of the kis-kid locus derived from the R1 plasmid and its chromosomal homolog—the E. coli MazE antitoxin [ 105 ].…”
Section: Modes Of the Toxin-antitoxin System Cross-talkmentioning
confidence: 99%